Village Consultative Body's Contributions to Development in Balongdowo Village - Yatim, Moch; Sukmana, Hendra (Indonesian Journal of Cultural and Community Development, 2024)
Background: Village consultative bodies (BPD) play a vital role in promoting good governance at the local level. Specific Background: This study examines the implementation of BPD's roles in a specific village context, focusing on their effectiveness in enhancing transparency and participation. Knowledge Gap: Existing literature lacks exploration of the practical applications of BPD roles and their impact on governance across different regions. Aims: This research analyzes how BPD executes its responsibilities, emphasizing its regulatory functions. Results: Findings show that BPD effectively implements its regulatory roles, contributing to improved village governance through adherence to standard operating procedures (SOPs) and strong budgetary support from the local government. Novelty: This study highlights the collaboration between BPD and local government, providing a replicable model of good governance. Implications: The research emphasizes the need to strengthen BPD-local government relationships to enhance community welfare and suggests improving SOPs to achieve collective governance goals, contributing to the discourse on local governance effectiveness. Highlights : Effective Collaboration: Highlights the successful partnership between BPD and local government. Regulatory Functions: Emphasizes BPD's role in enhancing governance through established procedures. Community Impact: Illustrates the positive effects of BPD's actions on local welfare and development. Keywords: BPD, local governance, regulatory roles, community welfare, transparency